1999
DOI: 10.1902/jop.1999.70.11.1406
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Familial Patterns of Microbial Infection in Periodontitis

Abstract: The purpose of this article is to review approaches to the assessment of familial patterns of microbial infection and disease in periodontitis, and to identify statistical methods appropriate to such considerations of family data. Previous studies have provided evidence for the presence of familial aggregation of periodontal pathogens and periodontitis and have alluded to possible transmissibility of these organisms within families. Modern statistical techniques permit the appropriate analysis of the correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Considering the fact that most of the included studies were published in the past two decades, the overall prevalence of GR at ≥1 mm threshold remained almost unchanged from 2001-201095% CI: 75.06-92.43) to 201195% CI: 75.06-92.43) to -202095% CI: 63.39-95.80) as shown in Supplementary file S12. The observed marginal difference could be attributed to the variations in the sampling methods and the geographical distribution of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the fact that most of the included studies were published in the past two decades, the overall prevalence of GR at ≥1 mm threshold remained almost unchanged from 2001-201095% CI: 75.06-92.43) to 201195% CI: 75.06-92.43) to -202095% CI: 63.39-95.80) as shown in Supplementary file S12. The observed marginal difference could be attributed to the variations in the sampling methods and the geographical distribution of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…It could be attributed to the variations in the sampling characteristics, differences in the studied age groups, disparities in the distribution of the risk factors and confounders (Dye, 2012). Methodological variations such as the types of probes used, differences in the cut‐offs/threshold points to report the prevalence of GR and probing locations could have also potentially contributed to the heterogeneity between studies and made it difficult to compare the results (Irfan et al, 2001). A high degree of heterogeneity similar to present study has also been observed in previous prevalence systematic reviews (Bouziane et al, 2020; Pentapati et al, 2019) due to the geographic variations, changes in diagnostic criteria, and the methodological features.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Amano and coworkers have reported that both disease‐associated and nondisease‐associated genotypes exist in P. gingivalis , suggesting that there is a significant predominance of P. gingivalis with type II fimA in periodontitis patients (2). The discovery of highly leukotoxic clones of Actinobacillus actinomycetemcomitans (8) has inspired periodontal studies to identify clonal types (25, 43, 57, 88) and to trace the transmission pathways of high virulence clones in subgingival plaque (38, 42, 48, 91). Findings from recent studies indicate the possibility of replacement therapy, from virulent to avirulent clones of the periodontopathogen (47).…”
Section: Diversity Of Clonal Typesmentioning
confidence: 99%
“…Periodontal disease, the major cause of tooth loss in the general population of industrial nations (1,2), is a chronic inflammatory disease of the periodontium that leads to erosion of the attachment apparatus and supporting bone for the teeth (3) and is one of the most common infectious diseases of humans (4). The obligately anaerobic Gram-negative bacterium Porphyromonas gingivalis has become recognized as a major pathogen for adult periodontitis (5).…”
mentioning
confidence: 99%